Bone Defect of the Tibia: A Case Report - Andriessanto Lengkong; Djarot Noersasongko; Haryanto Sunaryo; Tommy Suharso; Rangga Rawung; Stefan Kambey; Nurmalasari Amira (Medical Scope Journal, 2023)
Abstract: Defects in long bones including tibia are still difficult problems in orthopaedic field for both the physician and the patient. We reported a case of a 56-year-old woman who came to the hospital with the chief complaint of being unable to walk since she was nine years old after getting a motorcycle accident. The patient complained that her leg did not grow since then. The patient was fully conscious and hemodynamically stable. Physical examination revealed that there was a deformity of the left lower leg with shortening of the lower leg and absence of the tibial bone. The patient was diagnosed with left tibia bone defect, therefore, above-the-knee amputation was performed. The amputation must be viewed as an opportunity to re-establish or enhance the patient’s functional level and facilitate a return to near normal locomotion using a prosthesis after amputation. Soft tissue and muscle quality, bone condition, neurovascular conditions and function of the limb can be considered in the selection of therapy in bone defect. The level of amputation can be determined by assessing the bone condition, neurovascular condition, and the ability of muscle and skin flaps to close the wound. In conclusion, amputation can be the treatment of choice for patient with bone defect. Improving lower limb function is proven to maximize the patient quality of life. Keywords: bone defect tibia; above-the-knee amputation; transfemoral amputation